Cytochrome c biogenesis in bacteria - Sinha, N; Sinha, Neeti (1998)
﻿ Cytochromes c are electron transfer proteins in which haem is covalently attached to the polypeptide chain via thioether bonds formed from thiol groups of the two cysteines and the two vinyl groups of haem. This attachment is a post translational process and in many species of bacteria as many as approximately twelve gene products, the functions of which are largely unknown, are required. In Gram-negative bacteria the assembly of the c-type cytochromes occurs in the periplasm. Cytochrome c552 from the thermophilic organism Hydrogenobacter thermophilus is known to be expressed in the cytoplasm of Escherichia coli. This unique example of cytoplasmic assembly of a c-type cytochrome has previously been postulated to result from insertion of haem into the folded apoform of the cytochrome followed by non-catalysed attachment of the haem. This postulate is supported by the present work which has shown that the cytoplasmic assembly of this cytochrome c552 continues in the absence of the E. coli ccm genes which are needed for 'normal' c-type cytochrome assembly in that organism. Attempts to test the postulate of spontaneous assembly of the cytochrome c552 with in vitro experiments require large amounts of cytochrome c552 and its apo protein. A number of procedures for preparing these proteins were investigated. Although a T7-based expression produced lower amounts than was expected, its use led to detection of the apo form of cytochrome c552 in E. coli. It was shown that this apoform has some secondary structure, whereas mitochondrial apocytochrome c has a random coil conformation. This observation is consistent with, but does not prove, the postulate for cytochrome c552 assembly. It was unexpectedly found that a strain of E. coli that produces abnormally large amounts of its endogenous c-type cytochromes also made large amounts of cytoplasmic cytochrome c552. NMR studies on this material are consistent with a single and 'normal' attachment of the haem to the polypeptide. Thus the unusual cytoplasmic assembly was not different from the usual periplasmic assembly that occurs in the H. thermophilus itself. In E. coli there is a periplasmic cytochrome b562 that is presumed to acquire its haem in the periplasm. Some of the ccm genes, required for c-type cytochrome assembly, are postulated to code for a system that transports haem to the periplasm. Cytochrome b- 562 synthesis was not blocked by the absence of these genes. This implies that haem provision for cytochrome b562 synthesis occurs independently of the ccm system. Apocytochrome b562 could be detected in E. coli with the ratio apo:holo being higher in a strain that produces c-type cytochromes to relatively low levels. It is suggested that the synthesis of both cytochrome b562 and c-type cytochromes is at least partly a reflection of the rate of production of haem by the cells.